Vue. js 2 Design Patterns and Best Practices: Build Enterprise-Ready, Modular Vue. js Applications with Vuex and Nuxt - Halliday, Paul (Packt Publishing, Limited, 2018)
Vue.js is a lightweight and easy-to-learn JavaScript library for building user interfaces. With its faster and lighter Virtual DOM implementation, easier to learn, flexible, less opinionated solution, and many features, Vue.js is giving a good competition to the popular frameworks and libraries such as React and Angular. This book takes a.